Challenges and opportunities. (3rd December 2018) - Butler, Richard
Abstract : Purpose: This paper aims to identify key challenges and opportunities for tourist destinations in 2030. Design/methodology/approach: This paper is a discussion of literature on tourism futures and analysis of trends. Findings: That it is impractical to accurately make forecasts in terms of numbers, given external forces of change; the need to evaluate possibilities and opportunities likely to develop; tackling key issues such as climate change, political disturbance and overtourism. Practical/implications: This paper provides clarification of potential issues and problems and possible mitigating measures. Originality/value: The paper provides insights based on expert reading of the present.